Importance of Seismic Diffractions for Fractures Imaging - Bashir, Y. (Institute of Physics Publishing, 2017)
The use of diffraction imaging is important and rapidly gaining momentum in the oil and gas industry as the need of the industry moves toward exploiting smaller and more complex structures to find hydrocarbon. Illumination of these small scale discrete transmissivity structures such as faults or fracture zones prior to exploration offers substantial benefits for all phases of field development. We have established a new way of seismic imaging through diffractions study using reflection seismology. A subsurface geological model is developed from one of highly productive field located in the southern part of the Malay Basin. To study the seismic component in reflection seismology, a Finite difference modelling is used to generate synthetic seismic data. Both velocity and density models are used for the explanation of wave propagation, intimating the subsurface from side to side in both one-way and two-wave wave propagation. One-way wave equation migration methods are tested to image the faults in the synthetic seismic section of the Malay basin and we demonstrated the need of diffraction imaging for highly dipping faults and complex structure. © Published under licence by IOP Publishing Ltd.